Implementation of MikroTik RouterOS-Based Firewall to Enhance School Network Security Through Filter Rules and DoS Mitigation - Suryaningsih; Muliaty Yantahin; Muliadi; Abdul Muis Mappalotteng; Muh. Akbar (Journal of Smart Education and Emerging Technology, 2026)
Background/Context: Enhancing network security is very important to support activities that require networks in their implementation, especially in the field of vocational education. Objective/Purpose: This study aims to implement a MikroTik RouterOS-based firewall to enhance network security in the department of TJKT SMK Negeri 2 Gowa. Method: A quantitative experimental approach was employed in this study, with four tests, computer access testing, site blocking testing, educational site access testing, and stability and traffic testing. Usability was assessed using the ISO 9241-11 questionnaire involving 21 respondents, and the data were analyzed descriptively using a Likert scale. Results: The implementation results showed that the firewall on MikroTik RouterOS was able to enhance network security both based on technical aspects and usability evaluation results. Computer access testing found that the packet filtering firewall achieved a 100% success rate in restricting computer access according to the established rules. In content filtering, the firewall also achieved 100% success in blocking 13 non-educational sites while still allowing access to 7 educational sites through a combination of layer 7 protocols and address lists. Stability and traffic testing demonstrated the effectiveness of the raw firewall  in mitigating DoS attacks, system performance stabilized a bandwidth of 12.84 Mbps, latency of 55.2 ms, and 24% CPU usage. Conclusion: MikroTik RouterOS-based firewall received an average usability evaluation score of 3.81 (good category). Findings demonstrate the effectiveness of firewalls in improving network security in school laboratories based on the tested filter rules and DoS mitigation scenarios, thus supporting the network learning process.